Attitude Towards Green Products And Green Purchase Intention On The Green Purchase Behavior Of Detergent Products In The City Of Bengkulu - Apriyani, Neni; Salim, Muhartini; Santi, Fitri (The Manager Review, 2023)
The aim of this research is to determine the influence of knowledge of environmentally friendly products on environmentally friendly purchasing behavior, to determine the influence of attitudes towards environmentally friendly products on environmentally friendly purchasing behavior, and to determine the influence of environmentally friendly purchasing intentions on environmentally friendly purchasing behavior of detergent products in the city. Bengkulu. The research design is a survey. The population is the group studied, in this case the population of Instagram Info Bengkulu followers is 326,000 people. The sample for this research was 205 housewives in Bengkulu City who follow Bengkulu Info Instagram. Sampling was carried out using the accidental sampling method. The data analysis technique in this research is based on a reliable tool for testing models with a weak theoretical basis on data that experiences classical assumption problems. To test the influence of the PLS-based structural model through the inner model. The results of the research show that knowledge of environmentally friendly products has a significant effect on environmentally friendly purchasing behavior of detergent products in Bengkulu City and attitudes towards environmentally friendly products have a significant effect on environmentally friendly purchasing behavior of detergent products in Bengkulu City and environmentally friendly purchasing intentions have no significant effect on purchasing behavior environmentally friendly detergent products in Bengkulu City. has a significant effect on green purchase behavior for detergent products in Bengkulu City.